CONFLICT AND NEGOTIATIONS IN THE PUBLIC SPHERE - Szczepański, Marcin (Ekonomia i Prawo. Economics and Law, 2013)
System transitions taking place in Poland after 1989 entailed evolution in functioning of the public sphere, especially in relations of citizens and agencies representing them with administrative bodies. The formation of the civic society, an increase in the number of entities functioning in the public sphere, entering into various kinds of relations with administrative bodies and with similar organizations by such entities, diversification of the range of their activity, and at the same time their mutual dependence, have caused the negotiations to play more and more important role in such contacts. The article presents selected aspects of conflict and negotiations in the public sphere with the emphasis on factors bringing about typical difficulties.